Cytotoxic and anti-oxidant biphenyl derivatives from the leaves and twigs of Garcinia multiflora. (March 2017) - Tian, Dong-Song; Gu, Wei; Wang, Li-Ping; Huang, Lie-Jun; Rao, Qing; Huang, Tao; Fu, Yan-Hui; Zhang, Jian-Xin; Yuan, Chun-Mao; Hao, Xiao-Jiang
Graphical abstract: Highlights: Three new biphenyl derivatives were isolated from Garcinia multiflora . All eight isolated compounds showed weak cytotoxic activity against five human tumor cell lines. Three biphenyl derivatives showed moderate anti-oxidant activity with IC50 values ranging from 7.78 to 8.78 μ M. Abstract: Three new biphenyl derivatives (1 –3 ), together with five known compounds, were isolated from the leaves and twigs of Garcinia multiflora . Their structures were determined by extensive spectroscopic techniques including NMR spectroscopy and mass spectrometry. All eight isolates showed weak cytotoxicity on five human tumor cell lines. In addition, the three biphenyl derivatives showed moderate anti-oxidant activity with IC50 values ranging from 7.78 to 8.78 μ M.